Graffiti: a visual language and A tool of graphic design (Damascus University Journal for engineering sciences, 2021)
This paper focuses on both the common causes and factors that have strengthened the relationship between graffiti and modern graphic design. Where graphic design, the Internet and new digital technologies have changed the experience and meaning of graffiti in recent years, and focused on the strength of its symbols and characters, giving it an exceptional power to form one of the most important visual cultural elements in societies. For us, the street art represented by graffiti, graphic design and advertising design is an important part of our visual memory in the routine of everyday life. If we ask about the history of graffiti and graphic design and what is the relationship between them, we find that it is not possible not to circulate the culture of graffiti through interactive screens and modern designs that dominate today in the field of visual communication and multimedia. The computer screen has become the "new wall" of contemporary graffiti.
Keywords: graffiti; design, visual communications